2015
DOI: 10.1002/pros.22936
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile analysis of microRNAs in prostate cancer by next‐generation sequencing

Abstract: The small RNA transcriptomes obtained in this study uncovers six differentially expressed miRNAs and 12 novel miRNAs, and provides a better understanding of the expression and function of miRNAs in the development of PCa and reveals several miRNAs in PCa that may have biomarker and therapeutic potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 71 publications
3
41
3
Order By: Relevance
“…Previous studies have shown that the expression of miR-222-3p was up-regulated in prostate cancer and follicular thyroid cancer (Stokowy et al, 2014;Song et al, 2015). In addition, there is study reported that miR-222-3p was p53-regulated miRNA and its over-expression will inhibit the proliferation of neuroblastoma cells, which will contribute to the antitumor activity of p53 protein (Rihani et al, 2015).…”
Section: Cells In Vitromentioning
confidence: 94%
“…Previous studies have shown that the expression of miR-222-3p was up-regulated in prostate cancer and follicular thyroid cancer (Stokowy et al, 2014;Song et al, 2015). In addition, there is study reported that miR-222-3p was p53-regulated miRNA and its over-expression will inhibit the proliferation of neuroblastoma cells, which will contribute to the antitumor activity of p53 protein (Rihani et al, 2015).…”
Section: Cells In Vitromentioning
confidence: 94%
“…We previously investigated small RNA transcriptomes by deep-sequencing technology to evaluate three pooled libraries [9]. A total of 13,896,705, 16,768,094 and 17,184,337 raw sequence reads were produced for the malignant PCa (G > 7), early PCa (G ≤ 7), and BPH groups, respectively.…”
Section: Aberrant Expression Of Mir-141-3p In Human Early Pcamentioning
confidence: 99%
“…A total of 13,896,705, 16,768,094 and 17,184,337 raw sequence reads were produced for the malignant PCa (G > 7), early PCa (G ≤ 7), and BPH groups, respectively. After filtering out low quality reads and trimming off adaptors, 10,494,173, 14,577,221 and 14,614,835 sequence reads were obtained [9]. The normalized counts of sequencing reads (specific miRNA/total sequencing tags in the library) were used to quantify miRNA expression levels among the PCa (G > 7), PCa (G ≤ 7) and BPH groups.…”
Section: Aberrant Expression Of Mir-141-3p In Human Early Pcamentioning
confidence: 99%
See 2 more Smart Citations